Desenvolvimento e testes in vivo de nanopartículas de quitosana contendo insulina na cicatrização de feridas em ratos diabéticos - Ribeiro, Maycon Carvalho (2019)
Chitosan has been studied for its ability to accelerate healing and has been tested in the therapy of difficult-to-heal lesions, such as in diabetic patients. Insulin acts by stimulating the signaling pathway for wound healing. The objective of this work was to produce chitosan nanoparticles containing insulin for the evaluation of cicatrizant activity in diabetic rats. For the formation of the nanoparticles, the ionic gelation method was used. The nanoparticles were analyzed by diameter, potential zeta polydispersity index. The degree of deacetylation of chitosan by potentiometric was determined. For the insulin- associated nanoparticles, the mean diameter was 245.9 ± 25.46 nm and zeta potential of 39.3 ± 4.88 mV and PDI of 0.463 ± 0.01. The mean degree of deacetylation found was 72.95%. The Bradford assay revealed that the nanoparticles incorporated 97.19% ± 2.18 of insulin. To evaluate the healing, 72 Wistar rats were divided in four groups: sepigel (S), sepigel with insulin (SI), empty chitosan nanoparticles (QV) and chitosan nanoparticles containing insulin (IQ). The groups were subdivided into three subgroups (n = 6) according to the histological analysis times of the wound (3rd, 7th and 14th day). The induction of diabetes occurred through the intraperitoneal application of alloxan (120mg / kg). After confirmation of the diabetes state, the animals were anesthetized and the wounds were made with an 8.0 mm punch in the dorsal region. Macroscopic and microscopic analyzes were performed. It was possible to produce chitosan nanoparticles by the ionic gelation method, with desired diameter and zeta potential and polydispersity index. No differences were found in the rate of wound retraction among the four groups. The topical use of empty or insulin-containing chitosan nanoparticles in wound healing in diabetic rats was able to stimulate inflammatory cell proliferation and angiogenesis, followed by wound maturation. Differences in wound healing data from the group treated with insulin-containing nanoparticles and from the group treated with free insulin may be related to the high stability of the